(untitled) (Al Basirah, 2020)
The study focuses on the Islamic ideological discursive manifestations in the second language multicultural classroom as to how they are enacted. The ESL classrooms involve the classroom participants in learning the nonnative language through the explanatory discourses as enacted by their teachers. The classroom participants in any setting prefer their own socially constructed religious values. Since, classroom is a constituent of the social growing practices; the classroom approved practices contribute a substantial part in developing and establishing social norms in terms of ideological preferences. All the universities of the Islamabad were taken as the sites of the study where the undergraduate four-year English program is offered. The study is a census enquiry where all the population (students) of the sites is taken as sample of the study for data collection. The data were collected through, closed-ended questionnaires. It was found that the ideologies of the dominant groups are prevalent in the ESL undergraduate classrooms discursive practices. Although the classrooms have religious freedom; however, Islamic ideology prevails in terms of its practice and preference. In order to get plausible academic results in the ESL multicultural classroom, the teachers need to understand, perceive and sensitize themselves to the cultural, ideological and social understanding of the students for a smooth academic process in the language classroom.